2021
DOI: 10.3390/catal11030407
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Ethylene Polymerization with Bisarylimine Pyridine Iron (BIP) Catalysts

Abstract: The kinetics and terminations of ethylene polymerization, mediated by five bisarylimine pyridine (BIP) iron dichloride precatalysts, and activated by large amounts of methyl aluminoxane (MAO) was studied. Narrow distributed paraffins from initially formed aluminum polymeryls and broader distributed 1-polyolefins and (bimodal) mixtures, thereof, were obtained after acidic workup. The main pathway of olefin formation is beta-hydrogen transfer to ethylene. The rate of polymerization in the initial phase is invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 114 publications
0
15
0
Order By: Relevance
“…Complex 1 leads to a catalyst that yields HDPE in a range of 10–100 kDa. [ 53,54 ] This was initially considered a suitable component to form a processable blend with UHMWPE. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex 1 leads to a catalyst that yields HDPE in a range of 10–100 kDa. [ 53,54 ] This was initially considered a suitable component to form a processable blend with UHMWPE. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…Latter compound reacts with complex 1 and its products after MAO treatment to make it virtually inactive for polyethylene formation, either through coordination to the active site or by formation of soluble paraffins and alkenes by chain transfer processes. [ 54 ] Thus, any catalyst derived from 1 dissociating from the silica tends to become inactive for HDPE formation in solution. It is thus found that most of the HDPE was homogeneously formed on the immobilized silica@UHMWPE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This low temperature was chosen for the lower swelling of the polymeric product. Typical BIP FeCl 2 complexes like those based on ligands prepared from ortho alkyl substituted anilines become active ethylene polymerization catalysts in combination with MAO at such temperatures [57]. The expected color change from blue to orange did also not occur.…”
Section: Catalyst Synthesis and Product Characterizationmentioning
confidence: 92%
“…This indicates that the molecular weight is in the lower range for the action of catalyst 1. [61] A molecular weight determination by size exclusion chromatography was hampered by the presence of the silica particles. The elongation at break decreased from 33.2 ± 9.6 % at 0 wt% silica to as low as 15 ± 0.8% at 7.5 wt% silica.…”
Section: Mechanical Properties Of Bulk Materialsmentioning
confidence: 99%